Psychologists' experiences with telepsychology during the COVID-19 pandemic in South Africa - Anne S. Raju; Helene E. le Roux; Paul J. Pretorius; Omololu Aluko (AOSIS, 2024)
Background: During the COVID-19 pandemic, South African psychologists started to use telepsychology to continue providing services. However, diverse factors may influence psychologists' decisions regarding the use of telepsychology. Aim: To investigate South African psychologists' experiences with using telepsychology during the COVID-19 pandemic. Setting: Health Professions Council of South Africa (HPCSA)-registered psychologists practising in South Africa. Methods: A quantitative, cross-sectional study was conducted. Psychologists were invited to complete an online survey on the REDCap platform. Convenience sampling was used for respondent selection (n = 179). The study explored demographic variables, telepsychology use, changes in psychotherapy format, guidelines, ethical considerations, training, socio-economic factors, and individual patient and psychotherapist factors. Descriptive statistics, including categorical variables (frequencies and percentages) and numerical variables (medians and percentiles) were utilised for the data analysis. A bivariate analysis with backward selection was subsequently used, and significant variables were integrated into the logistic regression model. Results: Most respondents (84.8%) used telepsychology, with 72.8% considering it a positive experience. Private psychologists used electronic means for delivering services significantly more than public sector psychologists. The public sector psychologists had more challenges relating to changes in the therapeutic format, additional training requirements and technology access. Conclusion: During the COVID-19 pandemic, psychologists turned to telepsychology as a valuable tool for providing services while navigating the unique challenges it presented. Contribution: This study provides insights into the utility of telepsychology in the South African context during COVID-19. It underscores the experiences, importance of guidelines, and needs regarding training and technology access among psychologists.